PEMBUKTIAN PENGANJUR DALAM TINDAK PIDANA PEMBUNUHAN ANAK - Ulfa, Irene (Media Iuris, 2018)
The doctrine of inclusion as a basis for expanding the crime can be criminalized by a person who is involved in the realization of a crime. Participation is regulated in Article 55, Article 56 of the Criminal Code and Article 57 of the Criminal Code which means that there are two or more persons who commit a crime. The inclusion of (deelneming) in positive law is that there are two or more persons who commit a crime or in the words of two or more persons participating in a criminal act may be mentioned that a person participates in relation to another person (provided for in Article 55 and 56 of the Criminal Code). In Article 55 paragraph 1 to 2 of the Criminal Code, the Concept of the Occupation can be categorized as those who give or promise something by misusing power or dignity, by violence, threat or misdirection, or by providing opportunities, means or information, deliberately encouraging others to do deeds. The participation of advocates on the crime of child killing can be subject to accountability that has been regulated as Article 343 of the Criminal Code. Article 55 and Article 56 of the Criminal Code there are four forms of participation: a). order to do; b). participate; c). advocates / moves others to do; d). help do or help to do.